PENGARUH KEPEMILIKAN MANAJERIAL, LAVERAGE, DAN EARNING POWER TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA - Paniran Paniran; Agung Baharudin (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
This study aims to determine the effect of Managerial Leverage Ownership and Earning Power on Profit Management in Pharmaceutical Subsector Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The data used in this study used the quantitative method with the sampling technique using purposive sampling, the data used was 60 data. The data is taken from the financial statements and statistical data available from the idx website. The results of the correlation analysis of Managerial Ownership, Leverage and Power variables have a low level of relationship to earnings management. The results of the study partially the effect of managerial ownership has no effect on earnings management, leverage has no effect on earnings management, and earning power has no effect on earnings management. The results simultaneously state that there is no influence between managerial ownership, leverage and earning power variables on earnings management.